2017
DOI: 10.11604/pamj.2017.28.265.12703
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and association of demographic characteristics with malnutrition among children less than 24 months in Kwale County, Kenya

Abstract: IntroductionMalnutrition is an underlying cause of mortality in about half of the cases that occur among children less than five years in developing countries. In Africa including Kenya, this problem may be exacerbated by socio-demographic and socio-economic factors. This study aimed at determining nutritional status and association of demographic characteristics with malnutrition among children aged 1 day to 24 months in Kwale County, Kenya.MethodsA cross-sectional study was done in Mwaluphamba Location, Kwal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
5
12
1
1
Order By: Relevance
“…Regarding gender differences, it had previously been reported that boys were more vulnerable to health inequalities 6,9,10 . Our result was consistent with this.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding gender differences, it had previously been reported that boys were more vulnerable to health inequalities 6,9,10 . Our result was consistent with this.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding gender differences, it had previously been reported that boys were more vulnerable to health inequalities. 6,9,10 Our result was consistent with this. In Malawian culture, senior males are first to eat their meals, and children occupy a low position in the hierarchy.…”
Section: Discussionsupporting
confidence: 90%
“…The African continent has a high prevalence of malnutrition [ 42 ], and malnutrition has been linked to alteration in the gut microbiome. It is a major problem and sets up a vicious cycle of impaired immunity, increased risks for infections, and worsening malnutrition, especially in children with SCD who already have chronic ill health due to SCD.…”
Section: Main Textmentioning
confidence: 99%
“…According to the 2009 Kenya Demographic and Health Survey (KDHS), Coast Province, particularly Kwale County, one of the 47 Counties in Kenya, had a higher rate (39%) of malnutrition among children under 5 years of age than the national average; the second highest in the country. The 2014 Kenya Demographic and Health Survey (KDHS) shows that this has reduced over the years and was reported to be at 29.7% but was still the second highest in the country 9 . To improve health status of malnourished children under 5, Trnava University from Slovak Republic, established 3 nutrition centers in selected areas within Kwale County, because of the highest rate of malnutrition in children under 5 years of age and also the second factor of areas selection was the logistical location of the centers due to accessibility from the surrounding communities.…”
Section: Introductionmentioning
confidence: 99%